Validation of a Behavior Test for Predicting Puppies’ Suitability as Detection Dogs - Lazarowski, Lucia (Animals (Basel), 2021)
SIMPLE SUMMARY: The ability to predict a puppy’s future working success is important for working dog programs to maximize the number of dogs placed in service and allocate resources to puppies most likely to succeed. This study evaluated the utility of a behavioral test for candidate detection dog puppies. Agreement between scores from different observers was high; demonstrating the reliability of the test. Scores based on dogs’ performance in the test were also consistent with scores derived from questionnaires completed by the dog’s trainers; demonstrating the validity of the test’s measures. Finally; puppies’ performance in the test predicted future selection as a working dog as early as three months of age. The results indicate that the behavioral test is useful for evaluating the potential success of detection dog puppies. ABSTRACT: Behavioral characteristics are the most influential factor in the success of a working dog. The need for highly capable detection dogs continues to rise; but reliable methods for early selection are lacking. The current study aimed to assess the reliability and validity of a behavioral test for assessing detection dog suitability. A cohort of candidate detection dog puppies (n = 60) were tested at 3; 5; and 11 months of age; as well as at the completion of training at approximately one year. Tests were designed to assess important detection dog behavioral characteristics such as search ability and fearfulness. Inter-rater reliability was high between independent observers. Convergent validity was demonstrated by comparing Principal Component Analysis (PCA) scores from the behavior test to trainer ratings using the Canine Behavioral Assessment and Research Questionnaire (C-BARQ) and a survey of detection dog traits. Performance on the behavior test predicted adult selection as a detection dog as early as 3 months. The methods reported will be valuable for improving selection measures and enhancing collaborations across breeding programs in order to increase the availability of highly capable detection dogs.